SISTEM INFORMASI INVENTORY PADA PT. RUDY GASINDO UTAMA: Inventory, Tube, Data Management, PT Rudy Gasindo Utama, Report - Louis, Ahmad; Alvi Bakri, Nadia (JURNAL AKADEMIKA, 2019)
Inventory Information System is a system that is used to enter data on the procurement into the database, no error data management in input and report generation according to the desired data. Based on the survey and interview at PT Rudy Gasindo Utama, about informastion the existing system PT Rudy Gasindo Utama is still not using computerization optimally. This information system also features reports, tube input, tube outputs, and searches for tube data based on tube names. The existence of this Information System is expected to be useful for PT Rudy Gasindo Utama